Temperature-dependent Raman study of pure and silver nanoparticles dispersed N-(4-n-heptyloxybenzylidene)-4'-n-butylaniline (7O.4). Issue 3 (19th February 2019) - Mishra, Ramanuj; Bhattacharjee, Ayon; Bhattacharjee, Debanjan; Singh, Keisham Nanao; Alapati, Parameswara Rao
ABSTRACT: Temperature-dependent micro-Raman study of C-H in-plane bending mode of aromatic rings, C-N and C=N stretching of linking group (-C(H)=N) and C=C stretching of rings of pure and silver nanoparticles dispersed (0.5% and 1% by weight) Schiff's base liquid crystal (LC) compound, N-(4-n-heptyloxybenzylidene)-4'-n-butylaniline (7O.4) in 500–2250 cm −1 region has been done. The change in Raman spectral parameters (peak position and linewidth) at crystal–smecticG (K–smG) and smecticG–smecticC (smG–smC) gives the evidence of charge shift at phase transition which is associated with changes in orientation and vibrational freedom of the molecules. The peak position of the Raman bands shows blue shift for 0.5 wt% dispersed sample, whereas it shows red shift for 1 wt% dispersed sample. The blue and red shifts of the Raman bands indicate an increase and decrease in the charge density, respectively. The optimised structure and theoretical room temperature Raman spectra of 7O.4 were obtained using density functional theory. The vibrational assignment using potential energy distribution is reported using vibrational energy distribution analysis (VEDA). GRAPHICAL ABSTRACT: